Study and Characterization of Hydrochar from Duku (Lansium domesticum) Peel - Erni Salasia Fitri; Redo Ardiansyah (Indonesian Journal of Material Research, 2023)
Peel of duku fruit (Lansium domesticum) was prepared into hydrochar by using hydrothermal carbonation method at heating time variation of 8, 10, 12, 24 hours and temperature variation of 200 and 250°C. X-Ray Diffraction (XRD), Fourier Transform Infra Red (FT-IR), Brunauer Emmet Teller (BET) and Scanning Electron Microscope (SEM) analyses were conducted to determine at what time and temperature variations the adsorbent had the best adsorption quality. Based on the characteristics of the adsorbent, it can be seen that the best hydrochar is at 12 hours and at a temperature of 200°C. X-Ray Diffraction (XRD) analysis showed the presence of diffraction peaks at angles of 15.7° and 22.79° Fourier Transform Infra Red (FT-IR) analysis obtained explained that there were peaks of vibration peaks namely -OH, -CH, =CH, C=O, C=C aromatic and aliphatic. Brunauer Emmet Teller (BET) analysis can be seen that the increase in surface area on duku fruit peel (Lansium domesticum) and hydrochar at 200°C from 12.343 m2 /g to 22.635 m2 /g. Scanning Electron Microscope (SEM) analysis shows that the surface peel of duku fruit (Lansium domesticum) material has a clumped surface morphology in the same phase or also called aggregation, while the hydrochar tends to have an irregular shape or can be called heterogeneous morphology.